Assistance In Making Learning Media Based on Android-Based Educational Game Learning Media - Bambang Subiyakto; Herry Porda Nugroho Putro; Jumriani Jumriani; Mutiani Mutiani; M. Aditya Ramadhan; Ayu Kesuma Ramiadani (Journal of Social Development, 2023)
One of them is the use of smartphones in the field of education in the form of developing learning media in the form of educational games based on mobile devices. As described above, many users from mobile devices are considered very supportive of the application of educational games on mobile devices as learning media. This article describes training in making learning media with Android-based educational games. This community service was held from June 30 to July 14 2023. The location of community service is located in the city of Banjarmasin. The activity results describe an increased understanding of how making educational game learning media integrating local content cannot be done in one meeting. Therefore, in designing activities, a series of meetings is needed so that the knowledge related to making educational games becomes comprehensive.